Reliability‐based calibration of design code formulas: Application to shear resistance formulas for reinforced concrete members without shear reinforcement. (14th December 2022) - Slobbe, Arthur; Rózsás, Árpád; Yang, Yuguang
Abstract: This paper presents a reliability‐based calibration method for design code formulas. The method is demonstrated on the shear design formulas in Eurocode 2 and fib Model Code 2010 (MC2010). We found that the partial factor γ c in the current Eurocode 2 is about 20% lower than the optimal value and, thus, provides an insufficient safety margin. The obtained optimal partial factor γ R in the (modified) Eurocode 2 and MC2010 formulas is 1.53 and 1.36, respectively. The difference stems from higher accuracy and, hence, lower uncertainty of the MC2010 model in predicting experimental results. Hence, on average, the MC2010 formula leads to about 13% larger design resistances compared to Eurocode 2 given that the target reliability for both design formulas is the same. To stimulate and facilitate future structural code development and derivation of partial factors, we make the used computer code freely available.